EFFECT OF TIME OF INCUBATION ON NUCLEAR MATURATION AND CLEAVAGE POST IN VITRO FERTILIZATION OF ALPACA OOCYTES - Huanca L., Wilfredo (2014)
The study was carried out to evaluate the effect of incubation time on nuclear maturation and cleavage rate of alpaca oocytes after 72 hours post-fertilization. Cumulusoocyte complexes (CCOs) were collected from ovaries collected at slaughterhouse and transported in saline solution 0.9% with antibiotic antimycotic at 35 ºC. CCOs were aspirated from 2-6 mm follicles. Experiment 1: 502 oocytes were distributed in four maturation times (30, 34, 38, 42 hours), matured in TCM-199 supplemented with 10% fetal calf serum (FCS) (v:v), 0.5 μg/mL FSH, 10 μg/mL hCG, 0.2 mM sodium pyruvate, 50 μg/mL gentamicine and 1 μg/mL oestradiol, and cultivated at 39 ºC in an atmosphere of 5% CO2 and high humidity. After maturation, CCOs were removed from maturation medium and washed with PBS supplemented with 10% FCS and 1 mg/ml of hyaluronidase, and fixed in ethanol and acetic acid (3:1). Oocytes were placed on a glass slide, stained with 1% orcein and examined under microscope at 400x to evaluate nuclear maturation status. Experiment 2: 533 CCOs were culture under similar maturation protocols than experiment 1 and fertilized with epididymal spermatozoa. These were obtained by centrifugation at 700 g on a Percoll discontinuous gradient (22.5:45%) for 25 min. The supernatant was removed by aspiration and the pellet (containing viable spermatozoa) was re-suspended in TL Stock. Gametes were co-incubated for 18 h at 39 °C with 5% CO2 and cultivated in KSOM supplemented with 10% FCS (v:v), 0.2 mM sodium pyruvate and 50 μg/ml gentamicine, and evaluated in 72 hours. In experiment 1, 26.3±5.4, 52.6±6.7, 68.5±10.6 and 75.3±11.9% of oocytes were in M-II stage for the 30, 34, 38, and 42 h of culture respectively, with significant difference between 30 and 34 with respect to 38 and 42 h (p<0.05). In experiment 2, the cleavage rate was 9.5±4.8, 8.1±5.8, 15.6±9.2 and 19.8±8.0% for 30, 34, 38, and 42 h after culture, and without statistical difference between groups. These results indicate that is required 38-42 h for the maturation of alpaca oocytes.